Olfactory Communication of Sickness Cues in Respiratory Infection - Sarolidou, Georgia; Tognetti, Arnaud; Lasselin, Julie; Regenbogen, Christina; Lundström, Johan N.; Kimball, Bruce A.; Garke, Maria; Lekander, Mats; Axelsson, John; Olsson, Mats J. (Frontiers in Psychology, 2020)
Animals detect sick conspecifics by way of body odor that enables the receiver to avoid potential infectious transmission. Human observational studies also indicate that different types of disease are associated with more or less aversive smells. In addition, body odors from otherwise healthy human individuals smell more aversive as a function of experimentally induced systemic inflammation. To investigate if naturally occurring immune activation also gives rise to perceivable olfactory changes, we collected body odor samples during two nights from individuals with a respiratory infection as well as when they were healthy. We hypothesized that independent raters would rate the body odor originating from sick individuals as smelling more aversive than when the same individuals were healthy. Even though body odor samples from sick individuals nominally smelled more intense, more disgusting, and less pleasant and healthy than the body odor from the same individuals when healthy, these effects were not statistically significant. Moreover, raters filled out three questionnaires, Perceived Vulnerability to Disease, Disgust Scale, and Health Anxiety, to assess potential associations between sickness-related personality traits and body odor perception. No such association was found. Since experimentally induced inflammation have made body odors more aversive in previous studies, we discuss whether this difference between studies is due to the level of sickness or to the type of trigger of the sickness response.